Update on Medically Compromised Patients for Oral Surgery: The Bleeders and the Non-healers. (2nd March 2022) - Woolcombe, Sarah; Taylor, Talli; Renton, Tara
Abstract : Coagulation and wound healing following oral surgery procedures involve a number of intricate steps. The disturbance of normal physiological processes can be influenced by local and systemic factors that affect post-operative bleeding and healing of the surgical site. This article provides an update on medical conditions and medications, to aid identification of susceptible individuals, and describes the appropriate management of patients presenting with post-operative bleeding or a non-healing socket. CPD/Clinical Relevance: An understanding of post-operative bleeding and non-healing helps to prevent their occurrence and assists with optimal management when they do present.